A breakthrough land-use-based carbon accounting framework for multi-scale evaluation: Coupling optimization algorithm and LCA - Zhao, Jing; Xu, Shengnan; Ren, Yujie; Tang, Xiaolan (Sustainable cities and society, 2025)
•Established a standardized, land-use-based life cycle carbon accounting framework.•Industry and residential land uses dominate carbon emissions in construction and operation.•Zhoupu town's emission intensity: 606.56 tC/ha during construction, 344.92 tC/ha during operation.•Urban green spaces can achieve carbon neutrality approximately 8.5 years after operation.•Low-carbon land-use policies have been proposed based on the framework. Comprehensive, accurate, and efficient carbon accounting is essential for formulating carbon reduction strategies and assessing their effectiveness in urban areas. However, inconsistencies in carbon accounting results in urban areas often arise due to the lack of standardized methods, making the development of a unified, convenient, and multi-scale applicable carbon accounting framework critical. Currently, urban carbon accounting based on land use encounters challenges related to functional complexity, data barriers, and issues of precision and efficiency. To address these challenges, this study considered the spatiotemporal characteristics of life cycle carbon emissions and applied the optimization algorithm from operations research to derive the optimal distribution ratios of the employment population and various industry land uses, thereby overcoming the issues of functional complexity and data barriers in urban industry land uses. The equivalency factor method was utilized to construct a transportation carbon emission table, converting ground traffic volume into equivalent passenger car units, significantly improving carbon accounting efficiency. Local carbon emission factors were employed to further enhance the accuracy of carbon accounting. Based on these approaches, a unified, standardized, and multi-scale applicable urban carbon accounting framework was developed. Using Zhoupu Town in Shanghai, China, as a case study, the carbon emissions were calculated during the construction phase and over a one-year operational period. The research findings revealed that: a) Various industry and residential land uses were the primary carbon emission sources during both the construction and operational phases, with industry land uses contributing a larger share; b) Rail transit and public green spaces demonstrated considerable carbon reduction potential during the operational phase; c) The total carbon emissions in Zhoupu Town during the construction phase were approximately 2.59 MtC, and about 1.47 MtC over a one-year operational cycle. The average carbon emission intensity was 606.56 tC/ha during the construction phase and 344.92 tC/ha during the operational phase, and the carbon emissions per unit of building area were 180.69 kg CO2/m²; d) Urban green spaces could achieve carbon neutrality approximately 8.5 years after operation. The land-use-based life cycle carbon accounting framework developed in this study contributes to standardizing urban carbon accounting methods and supports regional carbon neutrality goals. [Display omitted]